Two dimensional heat transfer between two dissimilar materials using fourier series - Lin, Yiyang. (2012)
Heat conduction is classified into three main types; they are conduction, convection and radiation. The report will discuss about the working principles of different types of heat transfer. Followed by some of current methods available for solving these types of heat transfer problem, the author will then look into the possibilities of using Fourier series to solve the heat transfer problem.